PARADOKS PUJIAN DALAM BINGKAI CELAAN: ANALISIS STILISTIKA TA’KID AL-MADH PADA DESKRIPSI JANNAH DALAM QS. AL-WAQIAH DAN AN-NABA - Helga Juliya; Rasyid Hidayatullah; Akhmad Dasuki (JURNAL ILMIAH NUSANTARA, 2026)
This study examines the stylistic phenomenon of ta’kīd al-madh bimā yusyibihu adz-dzamm in the description of Jannah within QS. Al-Wāqi‘ah [56]: 25–26 and QS. An-Naba’ [78]: 24–25. The research aims to reveal the rhetorical structure, semantic function, and stylistic implications of paradoxical praise expressed through seemingly negative constructions. This study employs a qualitative library research method with a descriptive-analytical approach based on stylistics and Arabic rhetoric (balaghah), particularly ‘ilm al-badī‘. The primary data consist of Qur’anic verses containing negation and exception structures, while secondary data are drawn from classical and contemporary tafsir, stylistic studies, and balaghah literature. The findings demonstrate that the pattern of negation (nafy) followed by exception (istitsnā’) functions as a rhetorical strategy to intensify the praise of Paradise by emphasizing the absence of negative elements. This structure creates emotional engagement, reflective meaning, and aesthetic depth within the Qur’anic discourse. Furthermore, the integration of stylistic and balaghah approaches provides a more comprehensive understanding of the Qur’an’s linguistic beauty and semantic complexity, especially in interpreting eschatological verses related to Jannah.